2012
DOI: 10.1080/09291016.2011.571024
|View full text |Cite
|
Sign up to set email alerts
|

Delayed weekend sleep pattern in German infants and children aged 0–6 years

Abstract: In this study, parents of pre-school children (0-6 years) answered an online questionnaire (444 girls, 447 boys). Children's bedtimes are earlier before weekdays and later before weekend days, and this difference becomes greater with age suggesting an increasing social jet lag at an early developmental stage. Half of the children have a sleep-onset latency of 15 min or shorter. When asked for children's optimal wake/bedtimes, parents would prefer later weekend rise times but earlier bedtimes both during the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…There are small but significant gender differences with women scoring higher on morningness (Díaz-Morales & Randler, 2008;Randler, 2007). Also, age effects can be found with young children being more morning oriented at the kindergarten age (Randler, Fontius, & Vollmer, 2012) to morningness occurs (Roenneberg, Kuehnle, Pramstaller, Ricken, Havel, Guth, & Merrow, 2004) and people become progressively more morning oriented towards their later years of life (Randler & Bausback, 2010). Despite these common general patterns, significant inter-individual differences in chronotype remain throughout the lifespan.…”
Section: K-12 Distance Learningmentioning
confidence: 99%
“…There are small but significant gender differences with women scoring higher on morningness (Díaz-Morales & Randler, 2008;Randler, 2007). Also, age effects can be found with young children being more morning oriented at the kindergarten age (Randler, Fontius, & Vollmer, 2012) to morningness occurs (Roenneberg, Kuehnle, Pramstaller, Ricken, Havel, Guth, & Merrow, 2004) and people become progressively more morning oriented towards their later years of life (Randler & Bausback, 2010). Despite these common general patterns, significant inter-individual differences in chronotype remain throughout the lifespan.…”
Section: K-12 Distance Learningmentioning
confidence: 99%
“…The estimated percentage of people who fall within these preference categories varies from study to study, likely because of sample size, different scale cutoffs, and demographic composition. Furthermore, the majority of studies are conducted on student populations, which generally tend to show a stronger evening preference than the general population (e.g., Paine, Gander, & Travier, ; Randler, Fontius, & Vollmer, ). In an attempt to provide a more accurate assessment, Taillard, Philip, Chastang, and Bioulac () developed scale cutoffs more suited to the general population.…”
Section: Morning Larks and Night Owls: Circadian Rhythm Preferencesmentioning
confidence: 99%
“…26,27 Weekday-weekend variation is less prominent in young children than in adolescents and adults because of the prevalent morning chronotype as well as fewer social demands. 28 In our analysis, we found that large weekdayweekend variation in sleep schedules of young children was associated with high obesity risk, probably indicating that not all children were at equal risk of sleep variation. Children with parents suffering from obesity showed a larger shift towards later sleep schedules during the weekend than children with normal-weight parents.…”
Section: Discussionmentioning
confidence: 61%
“…While it may be somewhat arbitrary, the overall prevalence of unfavourable sleep characteristics in our study was in line with previous reports which have reported that 25–50% toddlers have experienced some sleep problems during the first years of life . Parents' own sleep discrepancies between weekday and weekend, which were not included in this study, may partially explain child weekday–weekend sleep variation . Furthermore, participants in the Early STOPP had higher education levels than the general population, which might impact the generalisability of study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation